2023
DOI: 10.1002/adsu.202300366
|View full text |Cite
|
Sign up to set email alerts
|

Nature‐Inspired Depolymerization of Soda Lignin: Light‐Induced Free Radical Promoted Cleavage of β‐O‐4 Bonds

Kerem Kaya,
Armagan Atsay,
Hande Gunduz
et al.

Abstract: The development of sustainable valorization methods for lignin is a challenging task because the vast majority of the reported studies involve either harsh conditions or expensive transition metal catalysts. Inspired by the sunlight degradation of lignin compounds, known as lignin yellowing, the use of a commercially available cheap organic photoinitiator, namely, phenacyl bromide (PAB) is reported here, for the efficient cleavage of lignin model compound 2‐phenoxyacetophenone (2‐PAP) and for the depolymerizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 65 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…In another study, Reisner and co-workers successfully obtained BA by reacting a commercial PS foam with organic HAT catalysts, such as fluorenone and other aryl ketones, in conjunction with an acid catalyst (H 2 SO 4 ) in an O 2 atmosphere and visible light (Scheme 1C). 35 Inspired by these recent works and our long-term interest in utilizing ambient conditions for the photochemical valorization of waste polymer, 25 we investigated the efficacy of phenacyl bromide (PAB) as a metal-free photo-HAT reagent/catalyst in the degradation of waste PS foam under ambient conditions. We used ethyl acetate (EtAc) as an environmentally friendly solvent (Scheme 1E) and hypothesized that the photodecomposition of PAB under near UV light (365 nm) leads to the in situ generation of bromine and phenacyl radicals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, Reisner and co-workers successfully obtained BA by reacting a commercial PS foam with organic HAT catalysts, such as fluorenone and other aryl ketones, in conjunction with an acid catalyst (H 2 SO 4 ) in an O 2 atmosphere and visible light (Scheme 1C). 35 Inspired by these recent works and our long-term interest in utilizing ambient conditions for the photochemical valorization of waste polymer, 25 we investigated the efficacy of phenacyl bromide (PAB) as a metal-free photo-HAT reagent/catalyst in the degradation of waste PS foam under ambient conditions. We used ethyl acetate (EtAc) as an environmentally friendly solvent (Scheme 1E) and hypothesized that the photodecomposition of PAB under near UV light (365 nm) leads to the in situ generation of bromine and phenacyl radicals.…”
Section: Introductionmentioning
confidence: 99%
“…Light-induced methods to degrade waste polymers are sustainable alternatives to thermal methods. , Photochemical treatment of synthetic and natural waste polymers has recently become the main focus of scientists because of the lower energy requirements and greener nature, which meet the criteria of sustainability. , Although hydrogen atom transfer (HAT) reactions have always been a versatile tool for C–H bond chemistry, exploitation of light-induced HAT reactions for the degradation/valorization of waste polymers through oxidative C–C bond breakages has recently proved to be an effective and sustainable strategy. Moreover, recent photochemical studies have also demonstrated that halogen radicals can act as the HAT reagent and selectively abstract benzylic hydrogens under mild reaction conditions. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation